2020
DOI: 10.1371/journal.pone.0237607
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in incentive sensitivity moderate motivational effects of competition and cooperation on motor performance

Abstract: Established research has documented the pervasive influence of incentives (i.e., food, sex, money) on animal and human behavior. Additionally, motivational theories postulating intra-individually stable preferences for specific types of incentives (i.e., motives) highlight that effects of a given incentive are highly dependent on the motive disposition of the individual. Indeed, also research on motor performance has documented the interactive effects of motives and motive-specific incentives on motor outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In addition, a recent study from our own lab indicated that manipulating the presence of power incentives (i.e., one-on-one competition with an ostensible opponent) moderated the relationship of participants' power motive to their performance in dart throwing: If power incentives were present, a stronger power motive was related to less variable errors in dart throws (i.e., better performance). 36 In a number of aspects, the current findings go above and beyond this established line of research. First, to the best of our knowledge, the present study represents the first instance documenting the impact of the power motive on motor performance in a field (i.e., classroom) setting, highlighting that findings previously established in the lab [56][57][58]36 also translate to more applied, real world settings.…”
Section: Relationship To Established Researchmentioning
confidence: 64%
See 4 more Smart Citations
“…In addition, a recent study from our own lab indicated that manipulating the presence of power incentives (i.e., one-on-one competition with an ostensible opponent) moderated the relationship of participants' power motive to their performance in dart throwing: If power incentives were present, a stronger power motive was related to less variable errors in dart throws (i.e., better performance). 36 In a number of aspects, the current findings go above and beyond this established line of research. First, to the best of our knowledge, the present study represents the first instance documenting the impact of the power motive on motor performance in a field (i.e., classroom) setting, highlighting that findings previously established in the lab [56][57][58]36 also translate to more applied, real world settings.…”
Section: Relationship To Established Researchmentioning
confidence: 64%
“…36 In a number of aspects, the current findings go above and beyond this established line of research. First, to the best of our knowledge, the present study represents the first instance documenting the impact of the power motive on motor performance in a field (i.e., classroom) setting, highlighting that findings previously established in the lab [56][57][58]36 also translate to more applied, real world settings. This is especially noteworthy, as such settings lack the advantage of rigorously controlling sources of unwanted error variance that render relationships that emerge in controlled lab settings harder to detect.…”
Section: Relationship To Established Researchmentioning
confidence: 64%
See 3 more Smart Citations